Territorial analysis of medical geographical conditions of Uzbekistan - Nilufar Kh. Komilova (Current Research in Behavioral Sciences, 2021)
The relevance of this study lies in the fact that the UN program says about the elimination of epidemics by 2030, the elimination of epidemics of diseases such as AIDS, tuberculosis, malaria, as well as measures to combat hepatitis and other water-borne diseases. The purpose of this article is to analyze the medical geography of Uzbekistan and health problems. After covering the geographical features of morbidity and mortality in the country, the following conclusions were drawn. One of the achievements of the socio-demographic development of the Republic of Uzbekistan in recent years is the reduction in mortality in all age groups. During this time, the country's health care system was improved, attention was paid to the health of the population. Also, an increase in the number of young and middle-aged people in the population, a decrease in the birth rate has led to a decrease in infant mortality, maternal mortality and overall mortality. However, there are areas with higher rates (Tashkent, Tashkent and Andijan regions), which can be explained by their location at a transport hub and industrialization. The authors believe that the theoretical issues of medical geography, medico-geographical zoning and forecasting, the identification of nosogeographic regions and foci require further research in this area. In such studies, it is necessary to focus on the role of medical geography in the system of geographical sciences, which, in turn, refers to aspects of natural and socioeconomic geography and geoecology.